FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KOPING PASIEN KANKER DALAM MENJALANI TERAPI DI RUMAH SAKIT ISLAM IBNU SINA PEKANBARU - H.Jamhur " "; Nurul " Huda; Wasisto " Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The copping strategies are ways in which individuals in a feel completing the stress .The purpose of this study was to determine the factors associated with coping in patients cancer undergoing therapy in Islamic Hospital Ibnu Sina Pekanbaru. The design used in this research  descriptive correlative with cross-sectional design. This research was conducted in a Mina room Hospitalization involving 41 respondents. The sampling method used is purposive sampling. Measuring tool used is a questionnaire that has been tested for validity. The analysis used is univariate and bivariate test Ch- square. The results showed that there was significant relationship between the variables of self-efficacy with coping patients undergoing treatment (p value = 0.047). The results of this study are expected to be used as input for the hospital to pay more attention to cancer patients coping so as to improve the quality of service caring and facilitate patient comfort in therapy. Keywords              : Cancer , copping, optimism, self efficacy, social support